2021
DOI: 10.1111/ajt.16269
|View full text |Cite
|
Sign up to set email alerts
|

The lectin-like domain of thrombomodulin is a drug candidate for both prophylaxis and treatment of liver ischemia and reperfusion injury in mice

Abstract: Ischemia and reperfusion injury (IRI) can occur in any tissue or organ. With respect to liver transplantation, the liver grafts from donors by definition experience transient ischemia and subsequent blood reflow. IRI is a problem not only in organ transplantation but also in cases of thrombosis or circulatory disorders such as mesenteric ischemia, myocardial, or cerebral infarction. We have reported that recombinant human soluble thrombomodulin (rTM), which is currently used in Japan to treat disseminated intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…HMGB-1 has been reported as one of the DAMPs released from necrotic cells and hepatocytes in the case of liver IR insult, which leads to the activation of macrophages, followed by the production of proinflammatory cytokines ( 3 , 8 ). Our previous study revealed that the HMGB-1/TLR-4 pathway played a critical role in the process of liver IRI ( 5 , 6 ). To clarify how intraperitoneal PA administration affects the HMGB-1/TLR-4 pathway, HMGB-1 levels after the IR treatment were measured in the sera of PA and saline-injected mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HMGB-1 has been reported as one of the DAMPs released from necrotic cells and hepatocytes in the case of liver IR insult, which leads to the activation of macrophages, followed by the production of proinflammatory cytokines ( 3 , 8 ). Our previous study revealed that the HMGB-1/TLR-4 pathway played a critical role in the process of liver IRI ( 5 , 6 ). To clarify how intraperitoneal PA administration affects the HMGB-1/TLR-4 pathway, HMGB-1 levels after the IR treatment were measured in the sera of PA and saline-injected mice.…”
Section: Resultsmentioning
confidence: 99%
“…We used the established mouse model of partial warm liver IRI ( 5 , 6 ). Mice were anesthetized under isoflurane and injected with heparin (100 U/kg).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…rTM is a drug that is approved in Japan for the treatment of disseminated intravascular coagulation syndrome. It binds to HMGB1 via its N -terminal lectin-like domain and assists in the proteolysis of HMGB1 by thrombin [ 30 , 31 , 32 ]. This molecular mechanism inhibits the RAGE pathway and NF-kB phosphorylation, which have recently been reported to exert anti-tumor effects [ 21 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activated protein C then inactivates factors VIIIa and Va in the presence of protein S, which exerts anticoagulant effects [ 29 ]. Regarding its other functions, rTM binds to HMGB1 via its N -terminal lectin-like domain, and assists in the proteolysis of HMGB1 by thrombin, degrading HMGB1 to a less inflammatory form [ 30 , 31 , 32 ]. The antitumor effects of rTM have also recently been reported [ 33 ].…”
Section: Introductionmentioning
confidence: 99%